KNOX action in Arabidopsis is mediated by coordinate regulation of cytokinin and gibberellin activities. - Jasinski, S; Piazza, P; Craft, J; Hay, A; Woolley, L; Rieu, I; Phillips, A; Hedden, P; Tsiantis, M (2005)
The shoot apical meristem (SAM) is a pluripotent group of cells that gives rise to the aerial parts of higher plants. Class-I KNOTTED1-like homeobox (KNOX) transcription factors promote meristem function partly through repression of biosynthesis of the growth regulator gibberellin (GA). However, regulation of GA activity cannot fully account for KNOX action. Here, we show that KNOX function is also mediated by cytokinin (CK), a growth regulator that promotes cell division and meristem function. We demonstrate that KNOX activity is sufficient to rapidly activate both CK biosynthetic gene expression and a SAM-localized CK-response regulator. We also show that CK signaling is necessary for SAM function in a weak hypomorphic allele of the KNOX gene SHOOTMERISTEMLESS (STM). Additionally, we provide evidence that a combination of constitutive GA signaling and reduced CK levels is detrimental to SAM function. Our results indicate that CK activity is both necessary and sufficient for stimulating GA catabolic gene expression, thus reinforcing the low-GA regime established by KNOX proteins in the SAM. We propose that KNOX proteins may act as general orchestrators of growth-regulator homeostasis at the shoot apex of Arabidopsis by simultaneously activating CK and repressing GA biosynthesis, thus promoting meristem activity.